MENTAL HEALTH ISSUES: STRESS, ANXIETY, AND DEPRESSION IN DIPLOMA AND DEGREE HEALTH CARE STUDENTS (Journal of Medical & Health Sciences Review, 2025)
Background: All healthcare students face mental health issues and their prevalence varies across different educational programs, including Lady Health Visitor (LHV), Community Midwifery (CMW), and Generic Bachelor of Science in Nursing (GBSN). High rates of mental health issues among healthcare students necessitate urgent attention and intervention.Objective: To determine the frequency of stress, anxiety, and depression in diploma and degree health care students.Methods: A cross sectional study, conducted at public and private institutes of nursing at Karachi form November, 2024, February, 2025. The calculated sample size was 383. A convenient sample technique was used to collect data through a validated questionnaire, DASS-21. All GBSN, LHV and CMW Students were included while all the Nursing Interns and Post RN students were excluded.Results: Among total participants, 28.5 %, reported moderate level of stress. Majority of the participants, 47.5%, reported extremely severe level of anxiety, 25.6% reported moderate level of depression. A significant association was found between study discipline and stress levels (p = 0.004). Moreover, a significant was found between study discipline and Anxiety levels (p = 0.001). There was also significance found between study discipline and Depression levels (p = 0.001).Conclusion: The findings of study highlights the need of establishing the mental health services to best deal with the all kind of academic and environmental factors which lead to mental health issues (Stress, Anxiety, and depression). Furthermore, all healthcare educational institutions must prioritize student’s mental health and offer best resources to manage with these health issues.